Pregnant Females as Historical Individuals: An Insight From the Philosophy of Evo-Devo - Nuño de la Rosa, Laura; Pavličev, Mihaela; Etxeberria, Arantza (Frontiers in Psychology, 2021)
Criticisms of the “container” model of pregnancy picturing female and embryo as separate entities multiply in various philosophical and scientific contexts in the last decades. In this paper, we examine how this model underlies received views of pregnancy in evolutionary biology, in the understanding of the transition from oviparity to viviparity in mammals and in the selectionist explanations of pregnancy in the frame of the so-called conflict hypothesis. In contrast, recent evo-devo studies on eutherian reproduction, including the role of inflammatory events and decidual cells, gather evidence in favor of considering pregnancy as an evolved relational novelty. Our thesis is that from this perspective we observe the emergence of a new historical individual in evolution. In evo-devo, historical units are conceptualised as evolved entities which fulfill two main criteria, their continuous persistence and their non-exchangeability. As pregnancy can be individuated in this way, we contend that pregnant females are historical individuals. We argue that historical individuality differs from, and coexists with, other views of biological individuality as applied to pregnancy (the physiological, the evolutionary and the ecological one), but brings forward an important new insight which might help dissolve misguided conceptions.